“GUMANTAN’’SISTEM PENGOBATAN MASYARAKAT DESA TELUK BERINGIN KECAMATAN GUNUNG TOAR KABUPATEN KUANTAN SINGINGI - Piko Wansahyu; Indrawati " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
Gumantan treatment is treatment that is performed by the shaman to heal the pain caused by supernatural powers by way of the real world to the supernatural . This study is located in Teluk Beringin Village sub district of Gunung Toar Kuantan Singingi District , Province Riau.The purpose of this study was to determine the system gumantan implement treatment systems Teluk Beringin Village community and to determine the public perception of the treatment system gumantan Teluk Beringin Village . The theory used is Max Weber's theory of social action , and supporting theory is a theory of perception , and Theory Parson ( AGIL ) , while the method used is qualitative data collection techniques purposive sampling to conduct interviews Observation and Documentation .The results showed that the community treatment system that is there are several ways in which the shaman to cure diseases caused by unseen forces , and there is also a public perception of treatment gumantan agree with such treatment , and the treatment is also very helpful gumantan people in curing diseases because the disease is a disease caused by supernatural powers that can not be cured by modern medicine .Keywords : Gumantan , Social Systems , Perception